1997
DOI: 10.1016/s1071-3581(97)90103-3
|View full text |Cite
|
Sign up to set email alerts
|

Left bundle branch block and coronary artery disease: Accuracy of dipyridamole thallium-201 single-photon emission computed tomography in patients with exercise anteroseptal perfusion defects

Abstract: This study confirms that dipyridamole is more accurate than exercise in excluding LAD coronary artery disease. However, there are still false-positive results and the severity of the septal or anteroseptal perfusion defect does not add additional information to identify LAD coronary artery disease. Coronary angiography is thus necessary for positive dipyridamole study results to identify coronary artery disease as a major prognostic factor in patients with LBBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 27 publications
1
22
0
3
Order By: Relevance
“…The two groups were studied together since both exhibit similar conduction characteristics on the ECG and secondly due to perfusion abnormalities not related to coronary artery disease that trouble SPECT analysis [8,10,23]. Only reports that carried information on the number of cardiac events in terms of prognosis were selected, whereas reports on the diagnostic accuracy of SPECT were left out.…”
Section: Search Of the Medline Database (January 1980 Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The two groups were studied together since both exhibit similar conduction characteristics on the ECG and secondly due to perfusion abnormalities not related to coronary artery disease that trouble SPECT analysis [8,10,23]. Only reports that carried information on the number of cardiac events in terms of prognosis were selected, whereas reports on the diagnostic accuracy of SPECT were left out.…”
Section: Search Of the Medline Database (January 1980 Tomentioning
confidence: 99%
“…However, in patients with an intrinsic left bundle branch block (LBBB) and in patients with right ventricular apical (RVA) pacing, its diagnostic accuracy and prognostic value is reduced [8][9][10][11][12]. False-positive perfusion defects in the septal region in intrinsic LBBB and in the inferoseptal wall in RVA pacing are the main causes of decreased diagnostic accuracy [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…22 Furthermore, perfusion defects are frequently visible on MPS in the absence of CAD. [10][11][12] These specific perfusion defects are at least partly caused by partial volume effects, thus limiting the value of this method. 9 In a previous study, we demonstrated that the cardiac prognosis of patients with LBBB and RVA-pacing is similar when AARD are present.…”
Section: Previous Studiesmentioning
confidence: 99%
“…5 The abnormal activation pattern frequently induces wall motion abnormalities, 5,6 abnormal wall thickening [7][8][9] and myocardial perfusion defects, 10 which hampers the diagnostic accuracy of non-invasive coronary risk-stratification with stress-testing. 9,[11][12][13] We recently demonstrated that combined perfusion/ contraction defects due to abnormal activation can easily be defined with gated myocardial perfusion single photon emission computed tomography (MPS) and in most cases can be distinguished from other causes of decreased regional myocardial 14 perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…LBBB is associated with an increased risk of cardiovascular morbidity and mortality and it may be a marker of slowly progressing ischemic or non-ischemic cardiac disease [2]. Non-invasive assessment of ischemic heart disease in patients with LBBB has been difficult in the past and invasive coronary angiography is often needed to confirm or defer obstructive CAD [3][4][5][6][7]. MSCT using 64-slice scanner has a high sensitivity and specificity when used for the evaluation of patients with LBBB and suspected CAD [8].…”
Section: Introductionmentioning
confidence: 99%